Religious and Ethnic Tolerance for Nation Building: A Challenge for Nigerian Leaders - Egwuanikwu, Mary Ifechukwude (NIU Journal of Humanities, 2023)
Nation building is a paramount issue that cuts across different facets of human society. It is a subject of interest among people of different ages, status, religious and cultural affiliations. It focuses on the available resources of the nation, that is, both human and material resources for the purpose of enhancing growth and development, which in turn, improves the well being of individuals in the society. Nigeria is a multi-religious, multi-ethnic, and multi- cultural nation with about one hundred and fifty million people amalgamated for the purpose of peaceful co- existence and nation building. Sadly, this has been a mirage due to religious and ethnic cleavages rooted in violence which have persistently threatened the very survival of the country as a nation. The article therefore examines how religious and ethnic tolerance can foster nation building in Nigeria for sustainable development. The study adopted sociological and historical approaches, and proposes that significant nation building can only be attained in a pluralistic society like Nigeria through religious and ethnic tolerance. The findings revealed that irresponsible leadership from among the political and religious ranks use religion and ethnicity as tools of oppression, rather than liberation. The work therefore recommended that for a meaningful realization of nation building, the religious leaders should desist from reckless acts of fundamentalism, embrace main values of tolerance, adopt a new approach of teaching, and emphasize those aspects of their beliefs that encourage peaceful co-existence in a pluralistic society. The Nigerian leadership must brace up with the challenge of spearheading the quest for nation building by being patriotic, not interfering in religious matters and sincerely cultivate a political culture that protects the rights of religious and ethnic nationalities. The paper concluded that Nigerian Christians and Muslims votaries together with the various ethnic groups should unite and tolerate one another irrespective of their differences for peace to blossom. Such act will promote unity in diversity and ultimate nation building and development. Keywords: Religion, Ethnicity, Tolerance, Nation Building, Nigerian Leadership